Exploring Self-Efficacy, Expressive Capabilities, And Social Leadership in Traditional Chinese Music Performance: A Study of Music Students in Henan Universities - Wang, Shuang; Fen, Beh Wen; Cheah, Kenny S.L (Journal of Cultural Analysis and Social Change, 2025)
This study explores the role of self-efficacy in enhancing expressive performance capabilities among music students specializing in traditional Chinese instruments at universities in Henan Province, China. It investigates how self-efficacy influences musical expression, emotional regulation, and performance confidence, particularly in a context where traditional technical training often outweighs emotional and psychological support. The research also examines the impact of teaching strategies, guided by a social leadership framework, in promoting students’ self-efficacy and expressive abilities. This study provides insights into how self-efficacy theory can be applied to improve expressive performance, reduce performance anxiety, and cultivate a more holistic approach to music education in under-resourced regions. The findings suggest that fostering emotional resilience and psychological readiness, through targeted instructional practices and supportive teacher-student relationships, is key to enhancing performance outcomes. By bridging the gap between technical proficiency and emotional expression, this research contributes to the development of more comprehensive music education models in traditional Chinese instrumental pedagogy.